Performing with Plants in the Ob-scene Anthropocene - Arlander, Annette (Nordic Theatre Studies, 2020)
Is there a way for the anthropocentric and anthropomorphic art form par excellence, the theatre, or performance art for that matter, to expand beyond their human and humanist bias? Is the term Anthropocene in any way useful for theatre and performance studies or performance-as-research? In the anthology Anthropocene Feminism (Grusin 2017) Rosi Braidotti proposes four theses for a posthumanist feminism: 1) feminism is not a humanism, 2) anthropos is off-center, 3) zoe is the ruling principle, 4) sexuality is a force beyond gender. These assertions can undoubtedly be put on stage, but do they have relevance for developing or understanding performance practices off-stage and off-center, such as those trying to explore alternative ways and sites of performing, like performing with plants? In this text, I examine Braidotti’s affirmative theses and explore their usefulness with regard to performance analysis, use some of my experiments in the artistic research project “Performing with plants” as examples, and consider what the implications and possible uses of these theses are for our understanding of performances with other-than-human entities, which we share our planet with.